Physical and Technological Parameters of Maize Varieties (Zea mays L.) Grown in the Southern Parts of Benin and the Influence of Chemical Composition - Semassa, Josiane Adjobignon; Anihouvi, Victor B.; Adjanohoun, Adolphe; Padonou, Wilfrid; Gbénou, Joachim D.; Lamine, Baba-Moussa (My University, 2016)
Objective: The study aims to investigate some physical and technological parameters of varieties of maize collected from the most representative areas of maize production in the southern part of Benin, and mainly used by the populations of those areas. Method: The chemical composition, physical and technological characteristics of the grains were determined using standard methods. Results: The results showed that the weight of 1000 grains ranges from 158.01 to 305.12 g, the length from 0.79 to 1.81cm, the average width from 0.74 to 1.51 cm, thickness from 0.36 to 0.85 cm and density from 1.07 to 1.25. Regarding the technological parameters, the hardness of the grains before and after cooking was between 16.78 and 47.20 kgf, and 0.23 and 0.71 kgf respectively, while the cooking time varies from 71.00 and 158.33 mn. There was a positive and significant correlation (r = 0.405; p < 0.026) between the hardness after cooking and the weight of 1000 grains, between the hardness after cooking and grain width (r = 0.460; p < 0.011). A positive and highly significant correlation (r = 0.527, p < 0.003) was also observed between the hardness after cooking and the grain length, between the hardness after cooking and the thickness of grain (r = 0.476, p < 0.008), and between the grain density and the weight of 1000 grains (r = 0.481, p < 0.007). A positive and highly significant correlation (r = 0.923, p < 0.000) wasalso observed
Keywords: Maize; Physical Characteristics; Technological parameters; Chemical parameters